Electronic properties of monolayer molybdenum dichalcogenides under strains. Issue 1726 (15th May 2015) - Sugimoto, J.; Shintani, K.
ABSTRACT: The electronic band structures of monolayer molybdenum dichalcogenides, MoS2, MoSe2, and MoTe2 under either uniaxial or biaxial strain are calculated using first-principles calculation with the GW method. The imposed uniaxial strain is in the zigzag direction in the honeycomb lattice whereas the imposed biaxial strain is in the zigzag and armchair directions. It is found that the band gaps of these dichalcogenides almost linearly increase with the decrease of the magnitude of compressive strain, reach their maxima at some compressive strain, and then decrease almost linearly with the increase of tensile strain. It is also found their maximum band gaps are direct bandgaps.